Selective Isolation of Multidrug-Resistant Pedobacter spp., Producers of Novel Antibacterial Peptides - Bjerketorp, Joakim; Levenfors, Jolanta J.; Nord, Christina; Guss, Bengt; Öberg, Bo; Broberg, Anders (Frontiers in Microbiology, 2021)
Twenty-eight multidrug-resistant bacterial strains closely related or identical to Pedobacter cryoconitis, P. lusitanus and P. steynii were isolated from soil samples by selection for multidrug-resistance. Approximately 3 to 30% of the selected isolates were identified as Pedobacter, whereas isolation without antibiotics did not yield any isolates of this genus. Next generation sequencing data showed Pedobacter to be on 69th place among the bacterial genera (0.32% of bacterial sequences). The Pedobacter isolates produced a wide array of novel compounds when screened by UHPLC-MS/MSMS, and hierarchical cluster analysis resulted in several distinct clusters of compounds produced by specific isolates of Pedobacter, and most of these compounds were found to be peptides. The Pedobacter strain UP508 produced isopedopeptins, whereas another set of strains produced pedopeptins, which both are known cyclic lipodepsipeptides produced by Pedobacter sp. Other Pedobacter strains produced analogous peptides with a sequence variation. Further strains of Pedobacter produced additional novel antibacterial cyclic lipopeptides (ca 800 or 1400 Da in size) and/or linear lipopeptides (ca 700 to 960 Da in size). A 16S rRNA phylogenetic tree for the Pedobacter isolates revealed several distinct clades and subclades of isolates. One of the subclades comprised isolates producing isopedopeptin analogues, but the isopedopeptin producing isolate UP508 was clearly placed on a separate branch. We suggest that the nonribosomal peptide synthases producing pedopeptins, isopedopeptins and the analogous peptides, may derive from a common ancestral nonribosomal peptide synthase gene cluster, which may have been subjected to a mutation leading to changed specificity in one of the modules and then to a modular rearrangement leading to the changed sequence found in the isopedopeptins produced by isolate UP508.